THE EFFECTIVENESS OF IMPERATIVE SENTENCES ON ENGLISH RECIPE BOOKS TO IMPROVE READING PROCEDURE TEXT TO THE NINTH GRADERS OF SMP AGUS SALIM SEMARANG ACADEMIC YEAR 2022/2023 - Ivani Nandarista; M. Wahyu Widiyanto; Fitri Yulianti (Melati Institute, 2023)
Reading is one of the most important English skills to explore information widely, increase knowledge and improve language skills. The effectiveness of imperative sentences in English recipe books has a good influence on students, to improve their reading skills on procedure texts. The purpose of this study was to determine the effectiveness of imperative sentences on students before and after treatment using procedure texts in English recipe books to find out substantial differences between the two. Researchers conducted quantitative research, and carried out in a one group pre-experimental style or can only be called using one class. The research sample was 26 ninth grade students of SMP Agus Salim Semarang. The research instrument is a test. There are two types of tests given, namely pre-test and post-test. After collecting the data, there was a significant difference between the effectiveness of imperative sentences on students before and after being given treatment using procedure text in English recipe books. The pre-test average score was 45.77 including the failed category and the post-test average score was 84.04 very good. The t-test result is 43 and the t-table value (5%; df=26) is 2.06. Thus, the t value is higher than the critical table value (43 > 2.06). To see whether there was a significant difference between the teaching methods using English recipe books before and after, the researcher conducted a t-test. The t-test value is determined through calculations using the t-test formula. The result is 43. Meanwhile, 2.06 is the critical number in the t table for the 5 percent alpha level and df = 25. 43 is the t value obtained. As a result, the value of t (43 > 2.06) is higher than the table's critical threshold. That is the success of students in the effectiveness of command sentences to improve reading of procedure texts. Therefore, Ha was approved.